Financial performance profile and evaluation of alternative equity management programs for farmers cooperative equity company - Smarsh, Andy (Kansas State University, 2010)
The goal of this thesis was to help Farmers Cooperative Equity Company (FCE) remain a firm, stable cooperative while increasing wealth of their patron owners. This thesis evaluated alternative equity redemption strategies to help FCE decide what decisions need to be made for proper use of equity for financing assets and increasing patronage returns. To develop an understanding of FCE and their current financial structures, we looked at the history of FCE and cooperatives in general. Then we gave a brief background of financial performance measures that were used to evaluate the profitability, solvency, liquidity, and efficiency of FCE. A cooperative performance profile was then run on FCE, by using a financial analysis program called PERFORM, to compare it to other agriculture cooperatives. The results for FCE were very strong in that they were performing at or above the 50th percentile range for many of the measures examined. FCE appears to be a very profitable, liquid, solvent, and efficient cooperative. We then used the results provided by the financial analysis program called PERFORM to make financial projections for the future to evaluate alternative equity redemption strategies for FCE. A computer program called FINPLAN was used to make the financial projections and evaluate the alternative equity redemption strategies. Five different strategies were evaluated and compared to the status quo, “strategy S0,” business as usual. The results showed that if the projections made for the future are correct, FCE would be able to return larger redemptions to patron owners by implementing an alternative equity redemption strategy that adheres to strict balance sheet management. Balance sheet management requires a cooperative to meet predetermined solvency and liquidity goals and then distributes the residual equity over and above that needed to finance assets, in combination with debt, as the equity redemption budget for that year. FCE could return larger redemptions while financing their operations through the use of patron equity and then return excess equity to patrons based upon cooperative usage. FCE’s general manager and board of directors have been provided with this thesis and the full project report. This thesis and project provide FCE with valuable information for them to make critical decisions on cooperative finance, including income distribution and equity management decisions.
Keywords: Agricultural Cooperative; Financial Performance; Income Distribution; Equity Management; Equity Redemption; Balance Sheet Management; Business Administration, Accounting (0272); Economics, Agricultural (0503)